Single particle movement analysis in a continuous flow fluid with magnetophoresis effect - Zahangir, Musanna; Ibrahim, Siti Noorjannah; Abdul Rani, Nabila Syafiqa; Abdul Malik, Noreha (IEEE, 2019)
This paper presents experimental results and modelling on the efficacy of magnetophoretic-based singleparticle. Magnetophoretic forces caused by the higher magnetic fields have been used to make movements of particle. A simple experimental microfluidic model was used to measure how well the movements could control the particle against laminar fluid flow. The particle movement control depends on the fluid velocity, hydrodynamics viscosity drag force, particle velocity and ferromagnetic wire magnetization with help of external surface source permanent magnet. This experimental model was developed by COMSOL Multiphysics® software. The AC/DC, Microfluidics and Particle tracing modules have been used in this Multiphysics software. Magnetophoresis force was simulated by the AC/DC module and the laminar flow in the microfluidic module was used to study the hydrodynamic drag force. The microfluidics and particles trajectory module have been combined to investigate the particles movements in the micro-channel. For experimental magnetization, minimum ranges were set at 106 (A/m) and higher ranges were set at 6.0×106 (A/m).